Tianjin’s Italian-Style town: the conundrum between conservation practices and heritage value - Jingting Wang; Maurizio Marinelli (Built Heritage)
Abstract The former Italian concession in Tianjin (1901–1945) has assumed symbolic significance for the modern urban redevelopment of this municipality through experimentation with distinctive practices of conservation management. In 1986, when the Historic Buildings Protection Area was defined, the former Italian concession was identified as a pilot urban conservation project. In 2002, the public company Haihe Construction and Development Investment Ltd. was put in charge of the design and implementation plan for the site, which progressively assumed the semblance of an ‘Italian-Style Town’. The distinctive transformation raised significant questions regarding the architectural restyling as well as its specific historical and cultural value. In August 2020, the management of the Italian-Style town was handed over to the Hebei District Government. This coincided with the emergence of a proposal for the creation of a ‘Larger Italian-Style Town’, that extended beyond the borders of the original Italian concession to include the former Austrian concession and the western section of the ex-Russian concession. The redevelopment strategy for this larger area aimed to create a service-oriented commercial area, presented as an ‘urban living room’, while showcasing Tianjin as an international metropolis. This article analyses the evolution of the conservation strategy as well as the relevant legislation, management, and practices during the redevelopment of the former Italian concession. The aim of this study is to address the conflict between heritage protection and commercialisation. Thus, this article offers a critique of the trend towards functional replacement and structural adaptation to cater to the tourism industry rather than to the value of the community’s livelihood as a living heritage.